Multilingual learning environments in early childhood education in Finland - Repo, Elisa (Suomen varhaiskasvatus, 2025)
Increasing linguistic diversity creates a need to construct early learning environments as spaces where children’s whole multilingual repertoires are represented. The purpose of these spaces is to support the crossing of linguistic boundaries during collaborative, play-based activities. In Finland, the language policies of the National Core Curriculum for Early Childhood Education and Care have been changed to promote multilingualism. This study focuses on data provided by early childhood education and care (ECEC) staff, documenting changing language policies in learning environments through the management of space and practice. The study analyzes what ECEC staff (N = 81 participant groups) report on constructing multilingual learning environments and what type of barriers and enablers are described as present in such environments. Theoretically, the analysis draws on pedagogical translanguaging. The data were collected using the LangPeda tool, and the participant groups’ textual documents were scrutinized via qualitative content analysis. The findings suggested that although most of the groups’ textual documents reflected either pre-planned or spontaneous pedagogical translanguaging, not all the groups were eager to change their monolingual practices. Linguistic hierarchies were found, and the development of children’s linguistic repertoires appeared to be hindered by misconceived understanding of language learning. Enabling pedagogical translanguaging to become part of ECEC institutions’ (spatial) practices requires sufficient resources, materials, and systematic education for ECEC staff.